Assessment of breast cancer disability: agreement between expert assessment and patient reports. Issue 8 (10th April 2017) - Letellier, Marie-Eve; Mayo, Nancy
Abstract: Objective : To estimate the extent of agreement between health professionals' (ClinRO) and patients' (PRO) ratings on disabilities associated with breast cancer (impairments, activity limitations and participation restrictions). Design : Cross-sectional. Methods : Health care professionals measured arm impairments, activity limitations and participation restrictions with the international classification of functioning (ICF) breast cancer core set. Participants filled five outcomes measures targeting health aspects of QOL that were previously mapped to the ICF. Agreement between ClinRO and PRO was estimated with quadratic Kappa. Results : About 245 paired clinician and participant completed the outcomes measures. A total of 60 items mapped to 24 different ICF breast cancer core set codes, which provide 68 analyses for agreement. Impairment was better addressed with PROs (mostly poor and fair level of agreement); Activity limitations, both PROs and self-reported outcomes (SRO) (fair); participation restrictions, PROs (fair). Conclusion : Clinicians usually underestimate the symptoms and impairments of the patients, leading to a greater proportion of poor agreement. PRO's provide valuable information on impairments at the mental function level and pain. ClinRO's provide more valuable information on physically assessed impairments (oedema). Activity limitations and participation restrictions, excluding reporting the difficulty aspect of various life situations, can be either SRO or ObsRO. Implications for rehabilitation: Impairments, activity limitation and participation restrictions are common sequelae of breast cancer treatment, which ultimately may affect the person's quality of life and should be investigated early on in the continuum of care. Clinicians should rely on the symptoms' reported by the patient regarding lymphedema and should identify the presence and severity of it. Patients inform best on the severity of pain, fatigue and mental distress experienced during and post-breast cancer treatment as clinicians tend to underestimate them. Clinicians and patients concur on presence and severity of activity limitations but not on difficulty, which can only be assessed from the patient's perspective.